Organizational Culture, Leadership dan Work Motivation Terhadap Employee Performance - Paulina Harun; Farizka Dinda Marsyandi (MDP Student Conference, 2022)
Abstract: The purpose of this study was to analyze the influence of Organizational Culture, Leadership and Work Motivation on Employee Performance. The sample used in this study found 30 permanent employees. In this study, data collection was carried out using primary data by distributing it in the form of Google Forms for permanent employees of PT. X. The data processing method in this study uses Partial Least Square (PLS) and is processed using the SmartPLS 3.0 application. The results of the analysis show that organizational culture has a positive and significant effect on leadership, organizational culture has a positive and significant effect on work motivation, leadership has a positive and significant effect on work motivation, leadership has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance. Leadership and work motivation also play a mediating role between organizational culture and employee performance. Abstrak: Tujuan penelitian ini adalah untuk menganalisis pengaruh Organizational Culture, Leadership dan Work Motivation terhadap Employee Performance. Sampel yang digunakan dalam penelitian ini berjumlah 30 orang karyawan tetap. Dalam penelitian ini, teknik pengumpulan data yang dilakukan adalah menggunakan data primer dengan menyebarkan kuesioner dalam bentuk Google Forms kepada karyawan tetap PT. X. Metode pengolahan data dalam penelitian menggunakan Partial Least Square (PLS) dan diolah dengan menggunakan aplikasi SmartPLS 3.0. Hasil analisis menunjukkan bahwa organizational culture berpengaruh positif dan signifikan terhadap leadership, organizational culture berpengaruh positif dan signifikan terhadap work motivation, leadership berpengaruh positif dan signifikan terhadap work motivation, leadership berpengaruh positif dan signifikan terhadap employee performance, work motivation berpengaruh positif dan signifikan terhadap employee performance. Leadership dan work motivation juga memainkan peran mediasi antara organizational culture dan employee performance